2001
DOI: 10.1046/j.1365-2222.2001.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between exhaled carbon monoxide levels and clinical severity of asthma

Abstract: Carbon monoxide (CO) can be detected in exhaled air and is increased in asthmatic patients not treated with corticosteroids. However, it is uncertain whether exhaled CO is related to severity of asthma. To study whether exhaled CO is related to severity of asthma in clinical courses, exhaled CO concentrations were measured on a CO monitor by vital capacity manoeuvre in 20 mild asthmatics treated with inhaled beta2-agonists alone, 20 moderate asthmatics treated with inhaled corticosteroids, and 15 stable asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 25 publications
4
40
0
2
Order By: Relevance
“…This study has provided most direct in vivo evidence that PM induce ROS generation and cause oxidative tissue damage. In humans, experimental DEP exposures result in increased CO in exhaled air; CO is the catalytic product of HO-1, which acts as a sensitive marker for PM-induced oxidative stress [69][70][71][72].…”
Section: The Impact Of Particulate Pollutants On Asthmamentioning
confidence: 99%
“…This study has provided most direct in vivo evidence that PM induce ROS generation and cause oxidative tissue damage. In humans, experimental DEP exposures result in increased CO in exhaled air; CO is the catalytic product of HO-1, which acts as a sensitive marker for PM-induced oxidative stress [69][70][71][72].…”
Section: The Impact Of Particulate Pollutants On Asthmamentioning
confidence: 99%
“…In 1972, Nikberg et al [5] were the first to describe exhaled CO (eCO) as a marker to assess different diseases such as cardiovascular diseases, diabetes, and nephritis. Moreover, high levels of eCO have been observed for many diseases [6,7], such as asthma [8][9][10][11] and cystic fibrosis [12,13], but these findings are still subject of controversy [14].…”
Section: Introductionmentioning
confidence: 99%
“…In two studies conducted by a Japanese group, the exhaled CO level was found to be higher in patients with asthma than in healthy individuals (2,3). In a meta-analysis that also referred to two studies conducted in Turkey (23,24), it was reported that the exhaled CO level was found to be higher in asthma patients who did not smoke than in those without asthma, and the CO level displayed a correlation with the severity of asthma (4).…”
Section: Discussionmentioning
confidence: 99%
“…CO is absorbed through smoking or can be produced endogenously in alveolar macrophages, endothelial cells, and other lung cells as a product of local inflammation and oxidative stress in individuals with airway diseases (1). In many studies, it was revealed that the end-expiratory CO (exhaled CO) level was higher in patients with severe asthma and lower in asthma patients receiving inhaled steroid therapy than in those not having therapy (2)(3)(4). Therefore, the exhaled CO level has recently begun to be used as an inflammatory biomarker in airway diseases such as asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis, and bronchiectasis (1,5).…”
Section: Introductionmentioning
confidence: 99%